Scientific Writing Training to Improve Professionalism Teacher at Vocational High School - Samsilayurni, Samsilayurni; Agustina, Mediarita; Nurlena, Nurlena; Utami, Sri (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
Scientific writing has become a requirement for a professional teacher, the aim of this community service is to increase teacher competence in preparing scientific written articles. The survey method uses a constructivist approach. The implementation of the activity is divided into two, first, the implementation of the activity is carried out by providing material in class using lecture, discussion, example and exercise methods, secondly, participants are provided with guidance services. The subjects of this service are teachers at Muhammadiyah 1 Palembang Vocational High School. The instrument used was a teacher understanding questionnaire about writing scientific papers. The results obtained in this activity were 86.50% of participants interested in the training carried out because they gained understanding and insight into article writing. Then, as many as 92.54% of participants stated that the material presented was understandable/clear. and 91.51% of participants stated that they were satisfied with the writing training which was carried out based on systematics and good language. So, it can be concluded that service activities with the theme of scientific writing training to improve the professionalism of teachers at Muhammadiyah 1 Palembang Vocational School provide new knowledge for teachers at the school related to publishing scientific papers in the form of scientific articles.